Investment strategy of sovereign wealth funds from emerging markets: the case of China - Cieślik Ewa (Bulletin of Geography. Socio-Economic Series, 2014)
Chinese sovereign wealth funds SWFs continue to expand rapidly and have become increasingly active in real-time strategic transactions recently. They have focused not only on financial markets in developed countries, but they also concentrate on commodity investment in emerging markets (mainly in African or Central Asian markets). The main goal of this paper is to examine investment patterns and performance of two large Chinese sovereign wealth funds: the State Administration of Foreign Exchange Investment Company (SAFE IC) and the China Investment Corporation (CIC). In the absence of official data on the activities of the funds, the article is based largely on press releases relating to the operation of funds and corporate reports of the companies invested in by the Chinese SWFs. The paper presents sectoral and geographical directions of China’s SWFs investment and tries to describe how the investment strategy of the aforementioned vehicles changed until mid-2013. The main limitation of the adopted methodology derives from the lack of information and poor transparency of the analysed vehicles. Moreover to obtain the correct information on the details of fund investments (size, value, date) each press release requires extensive verification.